The universality of Islam - Kahtany, Abdallah H. (Saudi Arabia The Islamic Educational Center, 2009)
"In the following chapters of this book, Islamic principles of equality, tolerance, solutions to problems facing humanity and position towards sciences and advancements will be compared to a number of contemporary ideologies and religions that may aspire for universality. The last chapter concludes with some of the major inherent principles of Islam as part and parcel of its teachings for the betterment of humanity."--Introduction.
Chapter one : Universality and equality. Christianity and equality -- The Jewish position towards other nations -- The socio-religious system of Hinduism -- Capitalism -- Islam and universal equality -- Chapter two : Universality and tolerance. The Crusaders' behavior in Palestine -- Christians and Jews in Palestine under Muslim rule -- Islam in Spain -- Christianity during the era of colonization -- Islam in Europe -- Islam in the Indian subcontinent -- Tolerance of Islam -- Concluding remarks -- Chapter three : Universality and promotion of science. Hinduism, Buddhism, and science -- Islam and science -- The impact of Muslim sciences on Europe -- The shallowness of modern science -- Why does Islam encourage science and advancement? -- Chapter four : Universality and solving problems of humanity. Alcoholism and drug addiction -- Crime -- Abuse of children and women.
Includes bibliographical references (pages [112]-[116])
Keywords: Islam; Islam -- Essence, genius, nature